Chinese environmental activism and the environmental politics of rumors. (May 2022) - Liu, Jingping; Lo, Kevin
Abstract: Rumors are an important yet poorly understood dynamic in environmental politics, particularly regarding their role in environmental activism. Drawing on theories of rumors, environmental information governance, and environmental activism, we analyzed the eco-politics of rumors in a Chinese village that experienced rumor-fueled protests against the construction and operation of a limestone quarry. We make three arguments regarding the condition, control, and content of rumors. First, poor environmental information governance, driven by a development-first and prejudice-rich official narrative and the strategic behaviors of blame and accountability avoidance, provides an important condition for rumor formulation and circulation. Second, the generation and circulation of rumors can be understood as a collective sense-making process driven by the informal communication between external and internal sources of information. The ephemeral nature of communication and group sanctions on government supporters make it difficult for authorities to control rumors. Third, by conceptualizing rumors as information warfare against official narratives, we show that rumors can foster a sense of collective urgency, reframe a land-right protest into an environmental protest that is politically more likely to succeed, and undermine public trust in local authorities. The findings suggest that rumors are an important part of environmental politics in China because of their role in environmental activism.